Smart agriculture system / Muhammad Azzam Idham Ali @ Anuar - Ali@Anuar, Muhammad Azzam Idham (2024)
The introduction of smart technology has transformed conventional agricultural techniques, opening the path for more efficient and sustainable farming methods. This final year project is to design a smart agriculture system that uses the capabilities of the ESP32 microcontroller to improve production, optimize resource utilization and promote environmental sustainability in modern farming. The ESP32 microcontroller serves as the system's primary control unit, seamlessly integrating a network of sensors, actuators, and communication modules. The system employs a varied variety of sensors, including soil moisture sensors, temperature sensors and humidity sensors. These sensors capture real-time data from the agricultural environment, allowing the system to work on its own whenever it needs it. The ESP32 uses wireless communication protocols such as Wi-Fi and Bluetooth to provide seamless interaction with a cloud-based platform. This connectivity enables farmers to remotely monitor and operate the whole system from a distance. The cloud platform saves and analyses the system's acquired data, providing significant insights into our farm. The ESP32 microcontroller, with its low cost, low power consumption and powerful processing capabilities, assures the system's dependability and energy economy. With the aid of ESP32, we can take proper care of our plants even when we are not present at our farm.